Plakophilin 1 in cancer: context-dependent dualism, subcellular dynamics, and therapeutic targeting - Huang, Yu-Mei; Zhang, Wen-Ling; Tang, Fa-Qing (Frontiers in Cell and Developmental Biology, 2025)
Plakophilin 1 (PKP1) is a desmosomal protein that plays a dual role in cancer, acting as either an oncogene or a tumor suppressor depending on the context. This review consolidates evidence regarding its mechanistic regulation via crucial signaling pathways, including Wnt/β-catenin, PI3K/AKT, and MAPK and underscores its potential as a clinical biomarker. The function of PKP1 is influenced by its subcellular localization: when membrane-bound, PKP1 stabilizes cell adhesion, whereas in the cytoplasm or nucleus, it facilitates oncogenesis by promoting MYC translation and modulating DNA damage. Phosphorylation events further refine this functional plasticity. Clinically, PKP1 expression is valuable for cancer subtyping and prognosis. This review also addresses unresolved questions concerning its regulation and suggests that future research in these areas could unlock the potential of PKP1 in precision oncology strategies.